2011
DOI: 10.4067/s0719-06462011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Some New Characterizations for PGL(2, q)

Abstract: Many authors introduced some characterizations for finite groups. In this paper as the main result we prove that the finite group PGL(2, q) is uniquely determined by its noncommuting graph. Also we prove that PGL(2, q) is characterizable by its noncyclic graph. Throughout the proof of these results we prove that PGL(2, q) is uniquely determined by its order components and using this fact we give positive answer to a conjecture of Thompson and another conjecture of Shi and Bi for the group PGL(2, q). RESUMENMuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In [14] and [17], it has been shown that Thompson's conjecture is true for some almost simple groups. Inspired by Thompson's conjecture, A. Camina and R. Camina come up with the following problem [10]: Problem.…”
Section: Introductionmentioning
confidence: 99%
“…In [14] and [17], it has been shown that Thompson's conjecture is true for some almost simple groups. Inspired by Thompson's conjecture, A. Camina and R. Camina come up with the following problem [10]: Problem.…”
Section: Introductionmentioning
confidence: 99%